2020
DOI: 10.1002/anie.202000173
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Endogenous Formate for Antibacterial Prodrug Activation by in cellulo Ruthenium‐Mediated Transfer Hydrogenation Reaction

Abstract: The abundance and evolving pathogenic behavior of bacterial microorganisms give rise to antibiotic tolerance and resistance which pose a danger to global public health. New therapeutic strategies are needed to keep pace with this growing threat. We propose a novel approach for targeting bacteria by harnessing formate, a cell metabolite found only in particular bacterial species, to activate an antibacterial prodrug and selectively inhibit their growth. This strategy is premised on transfer hydrogenation reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
0
22
0
2
Order By: Relevance
“…23−25 formate-dependent bacteria via transfer hydrogenation (TFH) using endogenous formate as the hydride source. 26 Since most antibiotics rely on ROS generation, specifically HO • , to induce bactericidal activities, we posited that it might be possible to uncover selective antibiotic metal complexes that could induce ROS by acting directly on intracellular O 2 to produce H 2 O 2 , a precursor for HO • via Fenton reaction, 3,4 using endogenous formate as a hydride source for targeted antibacterial therapy. However, O 2 TFH by traditional homogeneous catalysts is challenging particularly at low catalyst concentrations (μM) and ambient conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23−25 formate-dependent bacteria via transfer hydrogenation (TFH) using endogenous formate as the hydride source. 26 Since most antibiotics rely on ROS generation, specifically HO • , to induce bactericidal activities, we posited that it might be possible to uncover selective antibiotic metal complexes that could induce ROS by acting directly on intracellular O 2 to produce H 2 O 2 , a precursor for HO • via Fenton reaction, 3,4 using endogenous formate as a hydride source for targeted antibacterial therapy. However, O 2 TFH by traditional homogeneous catalysts is challenging particularly at low catalyst concentrations (μM) and ambient conditions.…”
mentioning
confidence: 99%
“…Metal-based complexes, through the versatility of their coordination chemistry, may open the door to new MOAs not found in organic scaffolds, such as ligand exchange, redox- or photoactivation, catalysis, or depletion of essential metabolites. To date, several metal-based complexes have been investigated in clinical trials and approved by the U.S. Food and Drug Administration for cancer, malaria, and neurodegenerative diseases. However, antimicrobial interventions remain a largely unexplored territory for metal-based complexes . We previously developed the coordination-driven three-component assembly (C3A) strategy to rapidly produce a diverse library of water-stable metallocompounds, Ru-arene Schiff-base (RAS) complexes, for the discovery of metallotherapeutic agents. From a panel of 768 unique RAS complexes, we also uncovered several leads that could selectively activate a sulfonylazide antibiotic prodrug within formate-dependent bacteria via transfer hydrogenation (TFH) using endogenous formate as the hydride source …”
mentioning
confidence: 99%
“…CuAAC and its related reactions have been successfully applied for biological macromolecule labeling, anticancer prodrug activation, bacterial metabolism labeling, and so on . Although polymer-based bio-orthogonal nanocatalysts , and some prodrug activation strategies are used for antibacterial applications, design and synthesis of a bio-orthogonal catalyst with recognition of specific target bacteria is highly desirable and urgent for in situ synthesis of antibacterial drugs.…”
mentioning
confidence: 99%
“…In particular, a number of groups have demonstrated that half-sandwich arene ruthenium complexes are some of the most suitable for in vivo usage. [30][31][32][33][34][35][36][37][38][39][40][41][42] In a pioneering example of this field, the Meggers group showed that Cp*Ru(COD)Cl (Cp* = η 5 -pentamethylcyclopentadienyl, COD = η 4 -1,5-cyclooctadiene) 1 could be used to facilitate allylcarbamate (alloc) cleavage within living mammalian cells. [30] Subsequent studies have shown that besides alloc deprotection, [31] Cp*Ru(COD)Cl can also be used effectively for azide-thioalkyne cycloaddition.…”
Section: Metal Catalyst Complexesmentioning
confidence: 99%